Efficacy of Allium sativum oil to alleviate tebuconazol-induced oxidative stress in the liver of adult rats - Berrouague, Salma; Rouag, Meriem; Khaldi, Taha; Boumendjel, Amel; Boumendjel, Mahieddine; Taibi, Faiza; Messarah, Mahfoud (Cellular and Molecular Biology, 2019)
The present study focused on the protective efficacy of Allium sativum oil (ASO) against tebuconazol (TEB)-induced oxidative stress in the liver of adult rats. Thirty-two rats were randomly divided into four groups of eight each: group I served as control rats, group II was treated with TEB (100 mg/kg bw), group III received ASO (5ml/kg bw). The animals of group IV were treated with TEB and ASO, during 4 weeks. The obtained results showed that TEB induced a significant change of some hematological parameters, including red blood cells (RBC), haemoglobin content (Hb), haematocrit (Ht), white blood cells (WBC) and platelet (Plt) compared to the control group. Moreover, while the total cholesterol levels and the activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and Î³-Glutamyltranspeptidase (Î³GT) significantly increased due to TEB administration, the concentrations of plasma total protein, albumin and triglyceride considerably decreased. Furthermore, the exposure to TEB significantly increased the malondialdehyde (MDA), protein carbonyl (PCO) and advanced oxidation protein products (AOPP) levels and decreased glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST) activities in the hepatic tissues. The results were confirmed by the histological impairments. Besides, the co-administration of ASO improved the status of all studied parameters. Therefore, our investigation revealed that ASO had protective effects against TEB-induced liver injury, which could be attributed to its phenolic compounds.